2013
DOI: 10.1542/hpeds.2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Connecting At-Risk Inpatient Asthmatics to a Community-Based Program to Reduce Home Environmental Risks: Care System Redesign Using Quality Improvement Methods

Abstract: We integrated environmental hazard mitigation into inpatient care. Community-engaged care delivery that reduces risks for poor asthma outcomes can be initiated within the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Studies have identified asthma phenotypes, or clusters, that are potentially amenable to more tailored medical care (39,40). Indeed, medication changes or optimization, such as targeted addition of antihistamines, allergen-specific immunotherapy (23, 24), or omalizumab; or referrals for in-home exposure assessment and remediation have the potential to reduce future exacerbations and improve asthma control (25)(26)(27). Initiation of in-home assessments may be particularly relevant given that reported exposures often differ from what is truly found in the home (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have identified asthma phenotypes, or clusters, that are potentially amenable to more tailored medical care (39,40). Indeed, medication changes or optimization, such as targeted addition of antihistamines, allergen-specific immunotherapy (23, 24), or omalizumab; or referrals for in-home exposure assessment and remediation have the potential to reduce future exacerbations and improve asthma control (25)(26)(27). Initiation of in-home assessments may be particularly relevant given that reported exposures often differ from what is truly found in the home (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Lowell, Massachusetts, an in-home environmental assessment and subsequent intervention to decrease triggers led to health improvements and cost savings for a population of low-income children with asthma (45). Locally, we have found success through relationships with health department housing inspectors (27) and a medical-legal partnership (46,47). Such interventions could play a significant role in the promotion of chronic asthma control for high-risk children.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Recent work with social services, public health officials, and legal aid advocates highlights the impact that such interventions can have for individual patients and populations. 36,[46][47][48] Enhanced, scaled partnerships of this sort may be especially relevant as health care reform pushes clinicians to find cost-effective methods for reducing health service utilization. 30 Nationally, identifying where social service and public health expenditures can be augmented may also prove impactful.…”
Section: Figurementioning
confidence: 99%
“…This document was used previously in our institution to increase referrals to a community program. 6,7 By reminding the physicians on admission, it ensured that the process started early in the patient's stay. A reminder was also built into the EMR-based attending handoff tool.…”
Section: Figurementioning
confidence: 99%